Professional AngularJS - Karpov, Valeri; Netto, Diego (Indianapolis, Ind. : Wrox, a Wiley brand, 2015)
A comprehensive guide to AngularJS, Google's open-source client-side framework for app development. Most of the existing guides to AngularJS struggle to provide simple and understandable explanations for more advanced concepts. As a result, some developers who understand all the basic concepts of AngularJS struggle when it comes to building more complex real-world applications. Professional AngularJS provides a thorough understanding of AngularJS, covering everything from basic concepts, such as directives and data binding, to more advanced concepts like transclusion, build systems, and auto.
When to Use MakeWhen to Use Grunt; When to Use Gulp; What Is Yeoman?; Getting Started with Yeoman; Scaffolding a New Project; Exploring Plug-Ins and Tasks; load-grunt-tasks; time-grunt; grunt-newer; grunt-contrib-watch; grunt-contrib-connect; grunt-contrib-jshint; grunt-contrib-clean; grunt-autoprefixer; grunt-wiredep; grunt-contrib-compass; grunt-filerev; grunt-usemin; grunt-contrib-imagemin; grunt-svgmin; grunt-contrib-htmlmin; grunt-ng-annotate; grunt-google-cdn; grunt-contrib-copy; grunt-concurrent; grunt-karma; Alias Tasks and Workflow; serve; test; build; default; Modifications
"Wrox programmer to programmer"--Cover.
Includes index.
Includes bibliographical references.
Online resource; title from PDF title page (Ebsco, viewed May 1, 2015).
Keywords: AngularJS (Software framework); Application software -- Development; JavaScript (Computer program language); COMPUTERS / Programming Languages / General; COMPUTERS / Internet / Application Development; AngularJS (Software framework); Application software -- Development; JavaScript (Computer program language); Electronic books; Electronic books; Electronic books